Intellectual property and U.S. relations with Indonesia, Malaysia, Singapore, and Thailand - Uphoff, Elisabeth (Southeast Asia Program, Cornell University, 1991)
Uphoff studies negotiations between the United States and Southeast Asian nations concerning intellectual property protection. She analyzes case studies showing how each of the ASEAN governments responded to American pressure to honor copyrights and patents. Her research is based on existing publications and interviews with government officials and scholars.